Risk factors for multidrug resistance in pulmonary tuberculosis patients with diabetes mellitus - Lianpeng Wu; Lianpeng Wu; Na Chen; Na Chen; Dandan Xia; Dandan Xia; Xiangao Jiang; Xiangao Jiang (Frontiers in Medicine)
ObjectiveThis study aimed to investigate the risk factors for multidrug resistance (MDR) in patients with pulmonary tuberculosis (PTB) and diabetes mellitus (DM), including those with and without prior TB treatment.MethodsA retrospective study was conducted from 1 January 2021, to 31 December 2023, at Wenzhou Central Hospital. Patients diagnosed with PTB and DM were included, with multidrug-resistant tuberculosis (MDR-TB) defined as resistance to at least rifampicin and isoniazid. Data on demographics, clinical symptoms, laboratory tests, and treatment history were collected. Multivariate logistic regression analysis was used to identify independent risk factors for MDR, and receiver operating characteristic (ROC) curves were constructed to evaluate the predictive value of these factors.ResultsA total of 318 patients were analyzed, with 253 in the non-MDR group and 65 in the MDR group. Significant independent predictors of MDR included a history of TB treatment, smoking, and elevated hemoglobin A1c (HbA1c) levels. ROC curve analysis showed that the combination of TB treatment history, smoking history, and HbA1c levels had an area under the curve (AUC) of 0.809, with 64.62% sensitivity and 82.61% specificity. In patients without prior TB treatment, smoking history and HbA1c were identified as independent risk factors, with an AUC of 0.771 for their combination. For patients with prior TB treatment, place of residence and pulmonary cavity were independent predictors, with an AUC of 0.802 for their combination.ConclusionThis study highlights the importance of smoking history, HbA1c levels, place of residence, and pulmonary cavity as risk factors for MDR in PTB and DM patients. Early identification of these risk factors can aid in the timely diagnosis and treatment of MDR-TB, potentially reducing its burden. Further research is needed to develop targeted interventions based on these findings.